Adaptation of Some Bread Wheat Cultivars to Kayseri Conditions - Sancar Bulut (Turkish Journal of Agriculture: Food Science and Technology)
Number of bread wheat cultivars have significantly increased in recent years and research on adaptation capacities of such cultivars are not sufficient in Kayseri. This study was carried out to determine high-yield bread cultivars able to adapt the conditions of Kayseri Province in 2010-11 and 2011-12 cropping seasons. A total of 42 national bread wheat cultivars were used and adaptation capacities were determined for Kayseri Region. Significant differences were observed in entire traits of the years and cultivars. Grain-fill periods of cultivars varied between 33.9-40.5 days, plant heights between 76.0-121.7 cm, number of spike per m2 between 292.5-645.8 spikes, number of kernel per spike between 17.4-43.9 kernels, 1000 kernel weights between 32.9-40.1 g, kernel yields between 153.0-278.3 kg/da, hectoliter weights between 72.8-78.4 kg and protein ratios between 9.08-14.37%. Considering the dry conditions of Kayseri region, Bezostaja-1, Gün 91, Bayraktar 2000, Dağdaş 94, Karahan 99, Tosunbey and Nenehatun cultivars were recommended for high yield and quality.